PATHS TO RESEARCH: A LITERATURE REVIEW ON THE REFORM OF SECONDARY EDUCATION, LAW 13.415/2017 - de Oliveira, Nara Rosane Machado; Ramos, Nara Vieira (Seven Editora, 2024)
This article presents data and reflections on the reform of secondary education, based on a systematic literature review carried out between September 2021 and January 2022. The objective was to search for the possible gaps left by the selected scientific articles, in order to understand which research paths are possible in the face of the high school reform. This is a qualitative, documentary-type investigation, based on journals from the CAPES Qualis System database (quadrennium 2013–2016, last evaluation available at the time of this investigation), in the area of evaluation in education. A1 journals whose databases were in Federal and State Universities, in the period from 2017 to 2021, were analyzed, using the descriptors "high school reform" and "new high school". We found a large production of works related to Law 13.415/2017, which shows a multiplicity of paths and themes of investigation, covering Brazil from North to South. These studies highlight the researchers' concern with cultural diversity, the diverse youth, the scarcity and precariousness of public schools, and the neglect and devaluation of the teaching profession, serving as a theoretical basis for many other ongoing studies. DOI:https://doi.org/10.56238/sevened2024.037-008